SECONDARY SCHOOL TEACHERS’ PERSPECTIVES ON AUTHORSHIP ANALYSIS IN THE CONTEXT OF AI-PLAGIARISM ON STUDENTS’ WORKS IN ENGLISH LESSONS - Suni, Fauziyyah Mufida; Maulidya, Rizka; Putri, Annisa Wahyu Dwi (International Journal of Instructions and Language Studies, 2025)
The rapid integration of Artificial Intelligence (AI) into educational environments has created new challenges for maintaining academic integrity, particularly concerning AI-assisted student work. As traditional plagiarism-detection tools prove insufficient against sophisticated AI-generated content, there is a growing need to explore teacher-driven detection strategies. This descriptive qualitative study addresses this gap by investigating teachers’ views on using authorship analysis as a method to identify AI-generated content in student assignments. The research utilised semi-structured interviews with ten secondary school teachers specialising in the English language. Data were analysed using thematic analysis. The findings revealed three primary themes: (1) The ELT Vulnerability to AI, highlighting an increasing concern about AI-assisted plagiarism in English language teaching; (2) The Resource Gap, where teachers express a lack of sufficient training and institutional resources to address the challenge effectively; and (3) The suggestion to combine AI detection tools, manual authorship analysis, and conversations with students as a strategy. The study highlights how institutional policies and the specific local educational context influence teachers' attitudes toward AI and academic integrity. There is a need to establish clear AI policies and promote AI literacy to students.